Evaluation of nutritive value of sugar cane bagasse treated with alkaline solutions through digestibility trial with sheep - Sonksen, Sylvia; Melotti, Laércio (Brazilian Journal of Veterinary Research and Animal Science, 1997)
Sugar cane bagasse (SCB) was immersed in water (B), or in sodium hydroxide solution 2% (D), or in wood ashes solution 30% (C), or it was suplemented with concentrate mixture containing buffers (A) to evaluate its nutritive value through an in vivo digestion trial. Twelve, male, castrated sheep were allocated in metabolic cages with sampling of total fecal output. Animals were assigned in a randomized block design. Dry matter and organic matter digestibilities of treatments were lower, and crude fiber showed higher values (p < 0.05). As a conclusion, treatment D was efficient to improve apparent crude fiber digestibility of the ration.